Metabolomics Based Comparison on the Biomarkers between Panax Notoginseng and its Counterfeit Gynura Segetum in Rats - Zhang, Yin; Zhang, Haixia; Shi, Jianfeng; Qiu, Shoubei; Fei, Qianqian; Zhu, Fenxia; Wang, Jing; Huang, Yiping; Tang, Daoquan; Chen, Bin (Current Pharmaceutical Analysis, 2020)
Background: Because of the similar appearance of Gynura segetum and panax notoginseng, the patients often mistakenly use Gynura segetum as Panax notoginseng, which causes serious liver damage. There is no comparative study on the metabolism of Gynura segetum and Panax notoginseng in the literature. This study was conducted to compare the difference between Panax notoginseng and its counterfeit Gynura segetum by using metabolomics method. Methods: In this paper, an ultra performance liquid chromatography coupled to quadrupole time-offlight mass spectrometric(UPLC-Q/TOF/MS) were used to detect the type of endogenous metabolites in urine and plasma of three groups (normal group, ethanol extract of panax notoginseng, decoction of Gynura segetum respectively, and different multivariate statistical analysis methods were established. Results: In this experiment, main urine biomarkers were L-glutamate, L-methionine, cytidine, and Ltyrosine in the Panax notoginseng group, which are phytosphingosine, creatine and sphinganine in the Gynura segetum group. The plasma biomarkers identified in the Panax notoginseng group were arachidonic acid, L-tyrosine, linoleic acid, alpha-linolenoyl ethanolamide and lysoPC (15:0), and in the Gynura segetum group are L-arginine, L-valine, arachidonic acid and LysoPC(18:2(9Z,12Z)). Conclusion: There are significant difference between Panax notoginseng and Gynura segetum in biomarkers from the perspective of metabolomics in the body.
Keywords: panax notoginseng